Pengaruh Cuka Salak (Salacca Vinegar)Terhadap Kadar Asam Urat Mencit (Mus musculus L.) Jantan Yang Diberi Diet Tinggi Asam Urat - Hafizh Alza Afra; Yusni Atifah (Jurnal Serambi Biologi, 2022)
The habit of eating fast food can cause various diseases in the body due to the presence of preservatives in these foods. By consuming foods that contain lots of purines and alcohol will increase the content of uric acid (gout) in the blood as the main cause of gout. Uric acid (gout) is produced by the body so that its normal presence in the blood, then (gout) or uric acid is formed as a waste of protein metabolism in foods containing purines. The purpose of this study was to determine the effect of salacca vinegar on uric acid levels in male mice (Mus musculus L.). This research is an experimental research. The research was conducted from August to October 2021 at the Zoology Laboratory, Department of Biology, FMIPA, Padang State University. The method or design used was Completely Randomized Design (CRD) with 5 treatments and 5 replications for each group. The data obtained were analyzed for variance or analysis of variance (ANOVA). The results of this study showed that a dose of 0.8 ml of salacca vinegar in treatment 1 (P1) gave the best results in reducing uric acid levels in male mice (Mus musculus L.). Based on the research that has been done, it can be concluded that the treatment of giving salak vinegar has an effect on reducing uric acid levels in male mice (Mus musculus L.).